Detection and Classification of Power Quality Disturbances Using Multiple Sequence Alignment (MSA) - Suwardono, Agus; S, Adi; P, Muridhi H (Nusantara of Engineering, 2014)
Abstract: In this paper, a Multiple Sequence Alignment (MSA) is implemented for automatic classification of power quality disturbances. The MSA technique is a way of arranging the three orÂ  more sequences of PQ disturbance. This technique can be use to identify regions of similarity between the sequences. The similarity is achieved at the smallest error of alignment. Aligned sequences of PQ disturbance are typically represented as a matrix. Twelve types of PQ disturbances based on IEEE are considered for the classification. The simulation results show that the Multiple Sequence Alignment (MSA) can effectively detect and classify different PQ disturbances. Â  Keywords: Multiple Sequence Alignment, Detection and classification of power quality disturbances. Â